Subjects Inside Out - Hoekstra, Teun (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1992)
AbstractThis paper argues that the notion of subject is purely syntactic, defined as an agreeing SPEC of a fonctional category. It is related to a theta-position inside a lexical projection by movement. It is furthermore argues that this particular conception applies not only to full clauses, but to all instances of predication, including secondary predication. This movement theory is contrasted with the indexing theory of predication. A new argument in favor of the movement theory is developed on the basis of floated quantifiers. Potentially problematic structures such as resultatives and nominalizations are shown not to be problematic for (small) clausal analysis of secondary predication.